Resource assignment optimization in design firms - K. Radwan; A. Elhakeem; E. Elbeltagi (Ain Shams Engineering Journal, 2024)
Resource allocation is a critical aspect of business operations that can significantly affect efficiency, quality, and profitability. In the context of design firms, the importance of resource allocation cannot be overstated, as it directly impacts the core operations and reputation of the business. However, despite its importance, resource allocation in design firms has received relatively scant attention in the literature, the paper aims to address this gap in the literature by proposing a resource allocation model specifically designed for architecture design firms. The developed model utilizes a Greedy algorithm approach to optimally allocate resources for specific design tasks, taking into consideration the qualifications and expertise of team members. By selecting the most suitable team members for each task, the model aims to maximize profitability and efficiency while minimizing costs. The study emphasizes the crucial role of resource allocation in architecture design firms and introduces a practical and adaptable optimization model, employing a Greedy algorithm approach to strategically assigning tasks and significantly improving profitability compared to random allocation methods. The findings contribute to addressing a notable gap in the literature on resource allocation within design firms and offering valuable insights for firms seeking to enhance operations and establish sustainable practices. The study is specific to architecture design firms, and future research could explore the model's impact on employees’ job satisfaction and the role of architectural management in influencing resource allocation practices.